Effects of extrinsic factors on some rumination patterns: A review - Abeni, Fabio (Frontiers in Animal Science, 2022)
Rumen and its activity, rumination, are the characterizing traits of suborder Ruminantia, with the related feeding habits and its consequent animal behavior. Several extrinsic (not related to the animal itself) factors affect rumination behavior; most of them are reflected in rumination timing (considering overall daily duration as well as circadian differences in rumination patterns): age, environmental factors, diet. For these reasons, great efforts have been sustained at research level for monitoring rumination patterns, Currently, some research outcomes are applied at farm level; other ones are still at experimental level. All these efforts are mainly finalized to the use of rumination patterns recording as an effective prediction tool for the early detection of health and welfare problems, both in a single head and at herd level. Moreover, the knowledge of the effects of extrinsic factor on rumination physiology represents a great challenge for improving the efficiency of ruminant livestock management, from the diet to housing system, from parasites to heat stress. The present review deals with the mainly worldwide raised ruminant species.